Interface engineering of advanced heterostructure through electrochemical synthesis for water splitting - Peng, Dongdong (Nanyang Technological University, 2021)
Green energy has played a key role in solving the current energy crisis and environmental issues. For various green energy resources including solar energy, wind energy, tidal energy, hydropower and so on, hydrogen produced from water splitting is abundant and cost-effective clean energy upon the active electrocatalyst. In this thesis, the electrocatalyst is prepared by electrodeposition that has been proven to be an economical, easy and efficient synthesis method when compared with other fabrication methods including solvothermal method and wet chemical method.